Analysis of community preparedness in facing fire disaster (case study of Sekaa Teruna Dharma Yowana, Pekutatan district, Jembrana-Bali) - Negara, Ni Luh Gede Aris Maytadewi; Dharmayanthi, Cokorda Istri; Listiantari, Dwiastutik (MEDIA ILMU KESEHATAN, 2024)
Background: Fire disasters are a significant risk during the dry season and prolonged drought conditions, Pekutatan is one of the sub-districts in Jembrana Regency, Bali, where most people are clove or coffee farmers. The risk of fire disasters in clove or coffee fields may occur because Bali is currently experiencing a dry season. Preparedness is an activity carried out to deal with disasters through quick and appropriate steps so that property loss and loss of life can be minimized.Objective: This research aims to determine the community’s readiness to face fire disaster.Methods: This research is descriptive quantitative research, where data was obtained from the results of fire disaster mitigation, with a purposive sampling technique where the sample consisted of 40 people. The research result was analyzed using descriptive analysis techniques.Results: The research results show an attitude of concern for disasters in the ready category (index value 87), emergency response plans in the ready category (index value 86), early warning systems in the ready category (index value 85), and resource mobilization in the ready category (index value 82).Conclusion: It can be concluded that the community is ready to mitigate fire disasters